Do racial inequities in infant mortality correspond to variations in societal conditions? A study of state-level income inequality in the U.S., 1992–2007. (September 2016) - Siddiqi, Arjumand; Jones, Marcella K.; Bruce, Donald J.; Erwin, Paul C.
Abstract: Background: Prior studies have examined the association between income inequality and overall infant mortality rates (IMR). We examine effects of income inequality on racial inequities in IMR over the period 1992–2007 in the U.S. Methods: Race-specific state IMR data were obtained from 1992 to 2007, from which absolute and relative IMR inequities were calculated. Fixed and random effects models, adjusted for state-level median income, percent poverty, percent high school graduates, and unemployment rate, were used to determine contemporaneous and lagged state-level associations between income inequality and racial IMR inequities. Results: Racial IMR inequities varied significantly across the U.S. Contemporaneous income inequality was negatively associated with white IMR only. Two-year lagged income inequality was negatively associated with black IMR and had the most pronounced effect on racial inequities in IMR. Discussion: Future studies should consider lagged effects of income inequality on IMR and other health outcomes, and should examine other potential societal conditions that may account for state-level variations in racial IMR inequities. Highlights: Infant mortality rates (IMR) varied across the United States between 1992 and 2007. Contemporaneous income inequality was associated white IMR; lagged income inequality, with black IMR. Lagged income inequality has most pronounced effect on racial inequities in IMR.